2011
DOI: 10.3109/00365521.2011.594087
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-binding lectin deficiency in pediatric patients with inflammatory bowel disease

Abstract: These data suggest that MBL deficiency may be associated with CD but not with UC in pediatric patients. The possible role of MBL in IBD requires confirmation in larger series and further investigation of the mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Of note, there is clinical and experimental evidence to support the role of MBL in limiting pathogen-induced mucosal damage. Although not without controversy, there are reports that MBL deficiency or low MBL levels are associated with IBD, at least in certain populations (26-28). It has also been shown that in a DSS-induced colitis model, MBL deficiency results in exacerbated colitis in response to normally mild gut pathogens (29).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there is clinical and experimental evidence to support the role of MBL in limiting pathogen-induced mucosal damage. Although not without controversy, there are reports that MBL deficiency or low MBL levels are associated with IBD, at least in certain populations (26-28). It has also been shown that in a DSS-induced colitis model, MBL deficiency results in exacerbated colitis in response to normally mild gut pathogens (29).…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies found an association between low levels of MBL and severe forms of CD but not CD overall or UC (62). MBL deficiency was also associated with pediatric CD (63,64), although the association with UC in these populations was inconsistent. Understanding how the immune system maintains homeostasis within the intestinal tract, as well as the rest of the body, is a major point of investigation for immunologists.…”
Section: Discussionmentioning
confidence: 99%
“…11 An association between MBL-deficiency and antiyeast antibodies (ASCA) is observed in Crohn's disease (CD), and this deficiency is frequently associated with a severe phenotype of CD. 12,13 Furthermore, CD patients are more frequently colonized by C. albicans than control subjects. 14 Experimental studies show that C. albicans aggravates intestinal inflammation induced by dextran sulfate sodium (DSS) in mice, and conversely, DSS colitis promotes C. albicans colonization.…”
Section: Introductionmentioning
confidence: 99%